Evolution of Labor Law in Kazakhstan: Overview and Commentary on Regulatory Objectives and Development - MUKHAMADIYEVA, Gulzhan N.; KALKAYEVA, Nessibeli; BOPABAEV, Ershat Ch.; SAILIBAYEVA, Zhanel Yu.; KHAMZINA, Zhanna A.; BURIBAYEV, Yermek A. (Journal of Advanced Research in Law and Economics; Vol 9 No 8 (2018): JARLE Volume IX Issue 8(38) Winter 2018, 2019)
This work is devoted to the review of the literature in the field of Kazakh legislation development, considering, firstly, different period, during which Kazakh labor law has been developing until present and, secondly, the extent to which the working law system, as can be seen, has fulfilled two of its basic principles. The article considers the previously unexplored question of the superiority of continental or Anglo-Saxon law in regulation of employment applicable to national conditions of Kazakhstan. The research demonstrates that Kazakh ‘labor law’ in formal sense has very few advantages from the perspective of its application for achieving goals. This, in its turn, indicates that to achieve more reasonable and accurate understanding of how and for what purpose labor is regulated in Kazakhstan some other approach is required. On the basis of current liberalization of regulation of working relations in order to accelerate the economic development, conclusions are drawn on the required directions and limits of the principle of the freedom of hired labor.